Paradigma Baru Balanced Scorecard : Peran Penting Perspektif Digital dan Keberlanjutan - Mardiyani, Nabilah; Biswan, Ali Tafriji (Journal of Applied Accounting And Business, 2025)
Digital transformation is fundamentally changing the way organizations design, implement, and evaluate performance measurement systems. The Balanced Scorecard (BSC), a framework that has been in use for more than two decades, is now in a reinvented phase to address the challenges of real-time analytics, big data, AI-driven decision-making, and the needs of digital organizations. This literature review examines the evolution and reinvention of the BSC based on 20 scientific journals (10 Scopus, 10 SINTA), while also mapping how the BSC concept evolved toward the Digital Balanced Scorecard (DBSC) in the sustainability aspect. The study shows that the BSC is not extinct but has undergone significant adaptations to incorporate digital metrics, technological capabilities, and sustainability integration. The analysis also identified research gaps related to the integration of the BSC with digital aspects and ESG-based digital performance. This study identified gaps in the integration of ESG metrics, digital capabilities, data governance, and dynamic performance systems. This study provides theoretical contributions in the form of a conceptual model of the digital BSC and recommendations for future research.